2009
DOI: 10.1136/ard.2008.106021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the oral application of a highly selective MMP-13 inhibitor in three different animal models of rheumatoid arthritis

Abstract: Objective To evaluate the decrease of cartilage destruction by a novel orally active and specifi c matrix metalloproteinase 13 (MMP-13) inhibitor in three different animal models of rheumatoid arthritis (RA). Materials and methods The SCID mouse co-implantation model of RA, the collagen-induced arthritis (CIA) model in mice and the antigen-induced arthritis model (AIA) in rabbits were used. Results In the SCID mouse co-implantation model, the MMP-13 inhibitor reduced cartilage destruction by 75%. In the CIA mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 37 publications
2
52
0
Order By: Relevance
“…The employment of an highly selective non-competitive inhibitor of MMP-13 (Johnson et al, 2007) significantly reduced the cartilage erosion in animal models of RA (Jüngel et al, 2010). The chondroprotective effects of micro-RNA inhibition of the MMP-13 expression was proved in human cartilage explants in vitro and through the development of inflammatory arthritis in mouse model in vivo (Akhtar et al, 2010).…”
Section: Neoplastic Diseasesmentioning
confidence: 98%
“…The employment of an highly selective non-competitive inhibitor of MMP-13 (Johnson et al, 2007) significantly reduced the cartilage erosion in animal models of RA (Jüngel et al, 2010). The chondroprotective effects of micro-RNA inhibition of the MMP-13 expression was proved in human cartilage explants in vitro and through the development of inflammatory arthritis in mouse model in vivo (Akhtar et al, 2010).…”
Section: Neoplastic Diseasesmentioning
confidence: 98%
“…51 In particular, MMP-1 and MMP-13 were reported to have a crucial role in the invasive properties of RASFs as shown in the severe combined immunodeficiency mouse co-implantation model. 52,53 Expression of MMPs is regulated by multiple pathways. DNA hypomethylation modulates expression of different MMPs in cancer cells.…”
Section: Dna Methylation Regulates the Expression Of Cxcl12 E Karouzamentioning
confidence: 99%
“…An MMP inhibitor that preferentially inhibits MMP-13 has been shown to block the degradation of explanted human osteoarthritic cartilage [11]. Recently published results showed the efficacy of a selective MMP-13 inhibitor to reduce cartilage degradation in the rabbit ACL model [12] and in some models of rheumatoid arthritis [13]. The selective MMP-13 inhibitor investigated in this study showed chondroprotective effects in the rat model of monoiodoacetate (MIA)-induced OA and in a surgical medial meniscus tear model [14].…”
Section: Introductionmentioning
confidence: 99%